Questioning the Accountability of Village Officials in Managing Village Funds: A Case Study in Karangan Dalam Village, Karangan District, East Kutai Regency, East Kalimantan - Nuuridha Matiin; Amirudin Amirudin (JASF: Journal of Accounting and Strategic Finance, 2023)
This study aims to apply stewardship theory to the analysis of village officials' roles in the planning, execution, administration, reporting, and accountability of village money. Officials from Karangan Dalam Village served as informants for this qualitative study. In planning efforts, the Secretary has created the Village Development Work Plan (RKPDesa) based on the questionnaires and stewardship philosophy. The village head receives submissions from the village secretary in the form of the village revenue and expenditure budget (APBDesa) and the village regulation work plan (Raperdes). The Village Consultative Body receives the Village Regulation Plan (Reperdes) Village Revenue and Expenditure Budget (APBDesa) for additional deliberation. The Village Fund Allocation (ADD) implementation provided information on the ADD manager's progress, particularly concerning fund absorption and physical activities. The person in charge of managing the village funds, the treasurer, keeps track of all income and expenses and neatly closes the books at the end of each month. Reporting on the management of village funds, the Village Head has sent the necessary SKPD to the regent, indicating the realization of budget utilization. Accountability for Village Fund Management: The village chief allocates the funds for the community, BPD, and regional government. The head of the village takes responsibility for overseeing the village's finances, and the ADD management has been operating well at the accountability stage. The head of the village consistently publishes the accountability outcomes of the APBDesa realization by the end of the relevant year. Village pages are still not being used to their full potential in terms of openness.